INTEGRASI KOMUNIKASI PEMASARAN DALAM KONSEP PARIWISATA BERKELANJUTAN “KAMPUNG ADAT SEGUNUNG” - Sheidy Yudhiasta; Garsione Agni Andrea; Leily Suci Rahmatin (Jurnal Riset Entrepreneurship, 2023)
This study examines the implementation of integrated marketing communication as a concept of sustainable tourism in Kampung Adat Segunung. The research methodology is qualitative. Data was collected by interviews, observations, and documentary studies. The participants in this research are divided into two groups, namely the key informants and the supporting informants. The key informants are the initiators who founded the "Kampung Adat Segunung" and the secretary. Meanwhile, the supporting informants are the owners of a micro, small, and medium enterprise in the "Kampung Adat Segunung. The findings indicate that Kampung Adat Segunung integrates promotion mix, such as advertising, personal selling, public relations, internet marketing, word of mouth, and events and experiences. This integration aims to provide consistent and coherent messages about the tourism potential, local culture, and sustainability to tourists. This study to underline integrated marketing communication as a concept of sustainable tourism that positively impacts the culture, and community of Kampung Adat Segunung.